The genus Phygasia Chevrolat (Coleoptera: Chrysomelidae: Galerucinae: Alticini) in Taiwan - Lee, Chi-Feng (Zootaxa, 2012)
The Taiwanese species of Phygasia are reviewed. Phygasia diluta Chûjô, 1963 is recognized as a valid species and is removedfrom synonymy with P. ornata Baly, 1876. It is a senior subjective synonym of P. taiwanensis Ge et al., 2010. The widely dis-tributed P. ornata Baly, 1876 is not found on the island of Taiwan but occurs on the Kinmen Island. A new species, P. chengi, parapatric with P. diluta, is described. A key to the Taiwanese species of Phygasia is provided.